FRET-Based Detection and Quantification of HIV-1 Virion Maturation - Sarca, Anamaria D.; Sardo, Luca; Fukuda, Hirofumi; Matsui, Hiroyuki; Shirakawa, Kotaro; Horikawa, Kazuki; Takaori-Kondo, Akifumi; Izumi, Taisuke (Frontiers in Microbiology, 2021)
HIV-1 infectivity is achieved through virion maturation. Virus particles undergo structural changes via the cleavage of the Gag polyprotein mediated by the viral protease, causing the transition from an uninfectious to an infectious status. The majority of proviruses in people living with HIV-1 treated with combination antiretroviral therapy are defective with large internal deletions. Defective proviral DNA frequently preserves intact sequences capable of expressing viral structural proteins to form virus-like particles whose maturation status is an important factor for chronic antigen-mediated immune stimulation and inflammation. Thus, novel methods to study the maturation capability of defective virus particles are needed to characterize their immunogenicity. To build a quantitative tool to study virion maturation in vitro, we developed a novel single virion visualization technique based on fluorescence resonance energy transfer (FRET). We inserted an optimized intramolecular CFP-YPF FRET donor-acceptor pair bridged with an HIV-1 protease cleavage sequence between the Gag MA-CA domains. This system allowed us to microscopically distinguish mature and immature virions via their FRET signal when the FRET donor and acceptor proteins were separated by the viral protease during maturation. We found that approximately 80% of the FRET labeled virus particles were matured with equivalent infectivity to wild type. The proportion of immature virions increased by the treatment of virus producer cells with a protease inhibitor in a dose-dependent manner, which corresponded to a relative decrease in infectivity. Potential areas of application for this tool are assessing maturation efficiency in different cell type settings of intact or deficient proviral DNA integrated cells. We believe that the FRET-based single-virion imaging platform will facilitate estimating the impact on the immune system of both extracellular intact and defective viruses by quantifying Gag maturation status.